Evaluation of the toxicology, anti-lipase, and antioxidant effects of Callistemon citrinus in rats fed with a high fat-fructose diet - Luis Gerardo Ortega-Pérez; Jonathan Saúl Piñón-Simental; Oliver Rafid Magaña-Rodríguez; Alejandro Lopéz-Mejía; Luis Alberto Ayala-Ruiz; Aram Josué García-Calderón; Daniel Godínez-Hernández; Patricia Rios-Chavez (Pharmaceutical Biology, 2022)
Context Callistemon citrinus Skeels (Myrtaceae) exhibits many biological activities.Objective This study analyzes for the first time, the toxicity, obesogenic, and antioxidant effects of C. citrinus in rats fed with a high fat-fructose diet (HFFD).Materials and methods Four studies using male Wistar rats were conducted: (a) 7 groups (n = 3): control (corn oil) and ethanol extract of C. citrinus leaf (single oral dose at 100–4000 mg/kg) for acute toxicity; (b) 2 groups (n = 8): control (corn oil) and C. citrinus (1000 mg/kg/day) for 28 days for subacute toxicity; (c) 3 groups (n = 4) with single oral dose of lipid emulsion: control (lipid emulsion), C. citrinus and orlistat (250 and 50 mg/kg, respectively) for lipid absorption; (d) 4 groups (n = 6): control (normal diet) and 3 groups fed with HFFD: HFFD only, C. citrinus and simvastatin (oral dose 250 and 3 mg/kg, respectively) for 13 weeks. Antioxidant enzymes and biomarkers were evaluated and inhibition of pancreatic lipase was determined in vitro.Results Toxicological studies of C. citrinus showed no differences in biochemical parameters and lethal dose (LD50) was higher than 4000 mg/kg. C. citrinus inhibited pancreatic lipase activity, with IC50 of 392.00 µg/mL, and decreased lipid absorption by 70%. Additionally, it reduced the body weight 22%, restored the activities of antioxidant enzymes, and reduced the biomarkers of oxidative stress.Conclusions Callistemon citrinus showed an effect against oxidative stress by reducing biomarkers and induced antioxidant system, without toxic effects.